2003
DOI: 10.1046/j.1365-2559.2003.01588.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of S100 calcium‐binding proteins in epidermoid cysts, branchial cysts, craniopharyngiomas and cholesteatomas

Abstract: This is the first study to report data on the expression of seven S100 proteins in different histopathological groups of epithelial head and neck lesions, whose precise embryological origins are still a matter of debate. S100 proteins could possibly be used as markers to target this embryonic origin, since our results show that S100A3 and S100A6 (and, to a lesser extent, S100A5) are expressed differentially across these different groups of epithelial lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Normally, the S100A5 protein is expressed in restricted areas of wildtype mouse brain . Expression of S100A5 was recently detected in epidermoid lesions and in the human kidney (Teratani et al, 2002;Pelc et al, 2003).…”
Section: Rt-pcr Analysismentioning
confidence: 98%
“…Normally, the S100A5 protein is expressed in restricted areas of wildtype mouse brain . Expression of S100A5 was recently detected in epidermoid lesions and in the human kidney (Teratani et al, 2002;Pelc et al, 2003).…”
Section: Rt-pcr Analysismentioning
confidence: 98%
“…Previous studies reported that S100A6 participates in cytoskeletal rearrangement and regulates cell cycle, intracellular calcium homeostasis and signaling, and ion transport [5][6][7]. Recent research has revealed that S100A6 is overexpressed in many cancer types, including melanoma [8], colorectal adenocarcinomas [9][10][11], gastric cancer [12], pancreatic ductal adenocarcinoma [13,14], astrocytoma [15], papillary thyroid carcinoma [16], choleteatoma [17], and osteosarcoma [18]. Increased S100A6 expression is also associated with the progression of tumors and could be used to predict the outcome of patients, such as pulmonary adenocarcinoma [19], pancreatic cancer [20], and gastric cancer [21].…”
Section: Introductionmentioning
confidence: 99%
“…In the cholesteatomas, the reactivity was strongest in the upper epithelial layers. The basal membrane was less positive (6). In our collective, the epithelial matrix of the EACC showed strong reactivity throughout all the layers.…”
Section: Discussionmentioning
confidence: 53%
“…They concluded that in contrast to S100B, the expression of S100A1, S100A2, S100A4 and S100A5 are often present in epidermoid cysts, branchial cysts, craniopharyngiomas and middle ear cholesteatomas. S100A3 and S100A6 (and, to a lesser extent, S100A5) were most dif-ferentially expressed across the different histopathological groups analysed (6). In the field of Otolaryngology, the external auditory canal cholesteatoma (EACC) is a very rare pathological entity (7).…”
Section: Introductionmentioning
confidence: 99%